Gerenciamento de diálogo baseado em modelo cognitivo para sistemas de interação multimodal - Prates, Jonathan Simon (Universidade do Vale do Rio dos Sinos, 2015)
Multimodal interaction systems allow a friendly use of computing systems. They allow users to receive information and indicate their needs with ease, supported by new interaction resources. In this context, the central element is the dialogue, established between users and these systems. The dialogue management of these systems involves various activities associated with the representation of subjects treated, possible answers, tasks model and users model treatment. In implementations for these approaches, some demands can be observed to approximate the results of the interactions by these systems of interaction in natural language. One possible line of action to obtain improvements in this aspect can be associated to the use of cognitive psychology studies on working memory and information integration. This work presents results obtained with a model of memory handling for multimodal dialogue interaction based on a cognitive model, which aims to provide conditions for dialogue generation closer to situations in natural language dialogs. This research presents studies that supported this proposal and the justification for the described model’s description. At the end, results using two prototypes for the model’s validation are also shown.
Keywords: Processamento de linguagem natural (Computação); Sistemas especialistas (Computação); Interação homem-máquina; Inteligência artificial; Natural language processing (Computing); Expert systems (Computing); Human-computer interaction; Artificial intelligence; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação